The determination of the in situ behaviour of backfill ribs in deep level gold mines - Adams, Duncan John (My University, 2016)
An understanding of the performance of uncemented backfills used for support in deep level South African gold mines is essential in evaluating the effectiveness of this support medium. Three main types of uncemented backfill material have been used for underground support in deep level gold mines. They are full plant de-watered tailings, full plant classified tailings and comminuted waste. The purpose of this dissertation is to document the data on the performance of all three of these types of backfill that have been collected at many underground sites, and to present an analysis of their general three dimensional behaviour.